Stem Cells in Veterinary Medicine—Current State and Treatment Options - Voga, Metka; Adamic, Neza; Vengust, Modest; Majdic, Gregor (Frontiers in Veterinary Science, 2020)
Regenerative medicine is a branch of medicine that develops methods to grow, repair, or replace damaged or diseased cells, organs or tissues. It has gained significant momentum in recent years. Stem cells are undifferentiated cells with the capability to self—renew and differentiate into tissue cells with specialized functions. Stem cell therapies are therefore used to overcome the body's inability to regenerate damaged tissues and metabolic processes after acute or chronic insult. The concept of stem cell therapy was first introduced in 1991 by Caplan, who proposed that massive differentiation of cells into the desired tissue could be achieved by isolation, cultivation, and expansion of stem cells in in vitro conditions. Among different stem cell types, mesenchymal stem cells (MSC) currently seem to be the most suitable for therapeutic purposes, based on their simple isolation and culturing techniques, and lack of ethical issues regarding their usage. Because of their remarkable immunomodulatory abilities, MSCs are increasingly gaining recognition in veterinary medicine. Developments are primarily driven by the limitations of current treatment options for various medical problems in different animal species. MSCs represent a possible therapeutic option for many animal diseases, such as orthopedic, orodental and digestive tract diseases, liver, renal, cardiac, respiratory, neuromuscular, dermal, olfactory, and reproductive system diseases. Although we are progressively gaining an understanding of MSC behavior and their mechanisms of action, some of the issues considering their use for therapy are yet to be resolved. The aim of this review is first to summarize the current knowledge and stress out major issues in stem cell based therapies in veterinary medicine and, secondly, to present results of clinical usage of stem cells in veterinary patients.